Political sophitication and the perception of power in International Relations. A semiotic approach - Grecu, Silviu-Petru; Chiriac, Horia Costin (Technium Social Sciences Journal, 2020)
The aim of this paper is to create a comprehensive image of power at the beginning of the XXI-st century. The research objectives are related to: i. the radiography of the perception of the political power regarding the main actors: USA, Russian Federation and China; ii. the identification of the relationship between global economy conditions, terrorist attacks and the dynamics of the political power in international arena; iii. the estimation of the magnitude of the statistical correlation between economic development, democratic order and the perception of the political power in international sphere. The research design is obviously quantitative, being based on descriptive statistics and linear and non-linear equations of regressions for estimating the main predictors and vectors which could influence the perception of the power. We use comparative case studies between USA, Russian Federation and China for exploring several associations between independent factors and the perception of the power and influence in the international context. Regarding the empirical findings, we have to stress that China’s power and influence are related with cyber-attacks from other countries (r = 0.707, p < 0.01) and USA’s power and influence are related with the conditions of the global economy ( r = 0.594, p = 0.01). Regarding the perception of the Russian Federation’s power and influence, we can observe linear associations with cyber-attacks (r = 0.605, p = 0.01) and flawed democratic order (r = 0.429, p= 0.02). Empirical findings reflect a new political geometry in the international arena, where the classical system is replaced by a multipolar model with two dominant political actors: USA and China. Synthesising, this article reflects the importance of the political perception and the political psychology in the sphere of international relations, where we can make the distinction between real and potential (or perceived) political power. This new geometry implies a new level of significance and a new semiotic strategy for interpreting both subjective and objective facts of the political world.